Prescribing Trends of Palliative Care Team's Use of Dexamethasone for Cancer-Related Pain. (2nd January 2018) - Barghi, Katayoun; Edmonds, Kyle P.; Ajayi, Toluwalase A.; Atayee, Rabia S.
ABSTRACT: Opioids are first-line therapy for cancer-related pain. In addition, corticosteroids are commonly utilized as adjuvant analgesics for pain and other symptoms in the oncology setting with limited supporting data. A retrospective analysis was conducted evaluating adult hospitalized patients receiving opioids who received once-daily dexamethasone on the recommendation of a specialty palliative care team during their hospitalization from January 1, 2015, to January 1, 2016. Primary end point was to describe prescribing patterns of dexamethasone in this patient population and secondarily examining any effect on oral morphine equivalent daily dose (MEDD), numeric pain score (NPS), and unwanted effects at 24 and 48 hours after the first dose of dexamethasone. Fifty-nine patients received an average dose of 13 mg (SD = 10) of dexamethasone for cancer-related pain, primarily acute pain ( n = 36, 61%). Many died before hospital discharge or soon thereafter ( n = 28, 47.5%). Although not statistically significant, our study shows a decrease of 23% and 19% in MEDD and NPS, respectively, without change in WBC after dexamethasone. A specialty palliative care team most often used once-daily dexamethasone for cancer-related pain in patients near the end of life. There were trends toward lower MEDD and NPS, but more robust studies are needed for validation.